Expression and clinical significance of Capase3 and C-IAP1/2 in ectopic endometrium of patients with endometriosis: Capase3 and C-IAP1/2 in endometriosis - Zhang, Xiaoyun; Zhao, Weiying (Cellular and Molecular Biology, 2023)
To analyze the expression of capase3 and C-IAP1/2 in endometriosis and their relationship with clinical practice. Ectopic and eutopic endometrial tissues were collected from women with endometriosis, and the control tissues were obtained from regular patients without endometriosis. The expression level of capase3 and C-IAP1/2 was detected by immunohistochemistry; in addition, the relationship between C-IAP1/2 expression and the clinical stage of endometriosis was analyzed. The expression of Caspase-3 in ectopic and eutopic endometrium was significantly lower than that in the control group (P < 0.005). The expression of C-IAP1/2 in ectopic and situ endometrium was significantly higher than in the control group (P < 0.005). The expression of C-IAP1/2 in stage III-IV was higher than in stage I-II endometriosis. The positive expression of c-IAP1 protein in ectopic endometrial tissue was negatively correlated with the positive expression of Caspase-3 protein in ectopic endometrial tissue (P<0.001). The low expression of Caspase-3 and the high expression of C-IAP1/2 in the ectopic endometrium and eutopic endometrial tissues compared with the controls. The results indicated that the apoptotic ability of eutopic and ectopic endometrium is weakened, which is involved in the pathogenesis of endometriosis. It is expected to be a target for the diagnosis and therapy of this disease. At the same time, the expression level of C-IAP1/2 is related to the stage of endometriosis, which can guide clinical treatment.